Bats as 'special' reservoirs for emerging zoonotic pathogens. Issue 3 (March 2015) - Brook, Cara E.; Dobson, Andrew P.
Highlights Bats experience morbidity to many extracellular but few intracellular infections. Bats control intracellular pathogens via cellular pathways to apoptosis/autophagy. These ROS mitigation pathways promote longevity and tumor avoidance. Extracellular pathogen-associated morbidity in bats results from immunopathology.